Judicial Self-‐Government as Experimental Constitutional Politics: The Case of Turkey - Çalı, Başak; Durmuş, Betül (German Law Journal, 2018)
This article traces the evolution of judicial self-government practices (JSG) in Turkey and argues that the frequent changes in JSG are part of a broader trajectory of experimental constitutional politics. The Council for Judges and Prosecutors has experienced sharp turns since its establishment in 1961, respectively in 1971, 1982, 2010, 2014 and 2017. During this period, Turkey experienced different forms of judicial councils ranging from co-option, hierarchical and executive controlled judicial council models to a more pluralistic model. The Justice Academy of Turkey has also not been immune from this experimentalism. The article discusses the endogenous relationship between these often short-lived experiments of JSG and their impacts on the independence, accountability, and legitimacy of the judiciary and public confidence in the judiciary. The article then turns to the repercussions of JSG on separation of powers and democratic principle. It focuses on the implications of the ambiguous position of the Council in the state structure for the separation of powers, and the revived debate on democratic legitimacy of JSG after the 2017 constitutional amendments.
CRIS-Team Scopus Importer:2024-06-28